Impact of global warming on dissolved oxygen concentrations in river Nile and on the waste allocation plan of the river (present and future plan) - Yassin, Rawnaa Imam (AUC Knowledge Fountain, 2016)
Water is the hub of life and driver of nature. That is why water quality is one of the most important concerns nowadays all over the world. Monitoring and improving water quality is considered as one of the key factors in the water quality management strategies. Water quality is extremely important to all countries and particularly in regions that depend mainly on water as a main source of life, like Egypt. The River Nile is a main source of life in Egypt. As much as water and water quality are of significant importance also climatic change and global warming have the same importance, it is one of the most investigated issues nowadays and definitely it is going to affect the future of mankind on earth. Global warming affects all aspects of life; i.e. humans, animals, water…etc. and this means it is affecting the ecosystem which in turn affects the whole life on planet earth and the most important that it has a great effect on water quality in rivers. That is why the aim of this study is to investigate the impact of global warming on river Nile water quality; especially on dissolved oxygen (DO) concentrations. The study is done on the Nile River in Egypt at three monitoring stations; namely at Luxor governorate, at Alexandria governorate and the Capital Cairo. A mathematical model is constructed to simulate the DO concentrations at different water temperatures. The study is investigating two scenarios; namely it simulates the critical DO concentration in summer (month August) where the Nile reaches its peak discharge in Egypt. Also it simulates the DO values in winter (month February) where the lowest discharge in the Nile in Egypt is reached. The study used air temperatures over the last 30 years to predict the Nile River water temperatures at the three above mentioned stations. Also in this research a mathematical model was developed to predict air temperatures from 2013 till 2030 and hence predict the values of water temperatures and DO concentrations for the same period of years (2013-2030).Also the further effect of global warming on the location of water and waste water treatment plants on the river Nile was studied. It was found that the values of the critical DO concentrations decreased over the years according to the global warming effects: at Luxor it decreased in February by 3.99% and by 4.26 % in August, In Cairo it decreased in February by 4 % and in August by 4.8 % whereas at Alexandria it decreased in February by 1.34% and in August by 5.16%. It is observed that global warming has a negative impact on the DO concentration values in the River Nile, according to the range of initial DO concentration values that were investigated for this study. DO critical concentrations values decreased significantly with the increase of air temperatures. Also it was found that global warming has a considerable effect on the locations of the water and waste water treatment plants on the river and thus on the waste allocation plan.